2017
DOI: 10.1103/physrevaccelbeams.20.123501
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order mode-based cavity misalignment measurements at the free-electron laser FLASH

Abstract: At the Free-Electron Laser in Hamburg (FLASH) and the European X-Ray Free-Electron Laser, superconducting TeV-energy superconducting linear accelerator (TESLA)-type cavities are used for the acceleration of electron bunches, generating intense free-electron laser (FEL) beams. A long rf pulse structure allows one to accelerate long bunch trains, which considerably increases the efficiency of the machine. However, intrabunch-train variations of rf parameters and misalignments of rf structures induce significant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Thus the amplitude excited by bunch tilt can be ignored. Also, compared to the beam offset, the trajectory tilt contributes much less to the dipole mode amplitude [16] and can be neglected. Therefore, the dipole mode amplitude can be seen in our case as only linearly related to the beam offset.…”
Section: B Experiments Setupmentioning
confidence: 99%
“…Thus the amplitude excited by bunch tilt can be ignored. Also, compared to the beam offset, the trajectory tilt contributes much less to the dipole mode amplitude [16] and can be neglected. Therefore, the dipole mode amplitude can be seen in our case as only linearly related to the beam offset.…”
Section: B Experiments Setupmentioning
confidence: 99%
“…Since there were different filter boxes being tested, a patch panel was used to quickly switch between cavities and boxes. Unlike the downconverter electronics design with a narrow band filter on the TE111 mode used by others [12,13], the HOM detectors' bandpass filters were optimized for two dipole passbands from 1.6 to 1.9 GHz, and the 1.3-GHz fundamental was reduced with a notch filter.…”
Section: B the Hom Detectorsmentioning
confidence: 99%
“…The cryomodule configuration with eight 9-cell cavities is currently the drive accelerator for the FLASH free-electron laser (FEL) [4], the European XFEL [5], the under-construction LCLS-II XFEL [6], the proposed MaRIE XFEL at Los Alamos [7], and the International Linear Collider (ILC) under consideration in Japan [8]. A recent study at FLASH using one specific TE111 HOM showed that the root mean squared (rms) relative alignments were about 342 µm for the 40 cavities in the 5 cryomodules with some close to 600 µm off axis [9]. The assessment of the effects on beam quality of such implementations warrants further study as the thrust for brighter electron beams at higher powers continues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations